Association between cesarean section and human capital in adulthood: 1982 and 1993 Pelotas birth cohorts, Rio Grande do Sul State, Brazil - Fernandes,Mayra Pacheco (2021)
Abstract: This study aims to assess the association between mode of delivery and human capital among young adults enrolled in the 1982 and 1993 Pelotas birth cohorts, Rio Grande do Sul State, Brasil. In 1982 and 1993, the maternity hospitals of the municipality were daily visited, the births identified, and those live births, whose family lived in the urban area of Pelotas, were examined and their mothers interviewed. Information on mode of delivery, vaginal or cesarean, was provided by the mother in the perinatal study. Performance in intelligence tests achieved schooling and income were evaluated in the 30 years visit at the 1982 cohort. At the 1993 cohort, schooling and income were assessed at the 22 years visit, whereas IQ was evaluated at 18 years. Tobacco smoking in adulthood and type of school was used as negative outcomes to strength causal inference. Initially, cesarean section was positively associated with human capital at adulthood, with the exception of income in the 1993 cohort. After controlling for confounders, the magnitude of the associations was strongly reduced, and the regression coefficients were close to the null value. The negative outcome analysis showed that, after controlling for confounding variables, the mode of delivery was not associated with tobacco smoking and type of school. Suggesting that the variables included in the regression model to control for confounding, provided an adequate adjustment and it is unlikely that the results are due to residual confounding by socioeconomic status. On the other hand, considering the short- and long-term risks and the epidemic of cesarean sections, measures should be implemented to reduce its prevalence.